13th International Malaysian Educational Technology Convention (IMETC) 2019 - Pusat Teknologi Pengajaran dan Multimedia, PTPM (Pusat Teknologi Pengajaran dan Multimedia, Universiti Sains Malaysia, 2019)
For this year, a number of different organisations have come together to plan and execute this auspicious conference, with a hope that the conference will reach out to a greater audience from diverse backgrounds. Teams from Malaysian Educational Technology Association (META), Resource and Educational Technology Division (BSTP), Ministry of Education Malaysia and Centre for Instructional Technology and Multimedia (CITM), USM have banded together and planned this prestigious event, and this year, Universiti Sains Malaysia (USM), Penang, Malaysia agrees to be the host. This year’s theme entitled ‘Inclusivity in the 21st Century’s Technological Teaching and Learning Environment’ is seen as timely, necessary, and consequential, as it envisions educators’ vital role in the future of learning. Technology alone is not enough to enhance students’ learning. This little fact has been largely recognised by educators and in recent times, we have seen an influx of initiatives carried by educators and governments around the world, providing instructive trainings and workshops to foster creativity and innovation in using technology, to not just deliver knowledge, but to also democratise the process of delivering the knowledge to a whole new level